Beyond the Scalpel: Addressing Communication and Distress in ENT Cancer - Bogdan Hirtie; Norberth-Istvan Varga; Andrada Oprisoni; Sonia Tanasescu; Estera Boeriu; Virgiliu Bogdan Sorop; Octavia Harich; Adrian Vasile Bota; Delia Ioana Horhat (Medicina)
Background and Objectives: Effective communication in oncology is crucial, but challenging due to the complex information and emotional burden associated with a cancer diagnosis. This cross-sectional study investigated the communication preferences of 155 Romanian adults diagnosed with ENT cancers and explored the relationship between these preferences, their levels of psychological distress, and sociodemographic factors. Materials and Methods: Participants completed the KOPRA questionnaire, assessing communication preferences, and the Hospital Anxiety and Depression Scale (HADS) to measure psychological distress. Results: The results revealed that patients strongly prioritized active involvement in their care (Patient Participation and Patient Orientation—PPO) and open communication with healthcare providers (Effective and Open Communication—EOC). While emotional support was valued, it was considered less critical than PPO and EOC. Notably, communication about personal matters was deemed the least important aspect of communication. A high prevalence of psychological distress was observed, particularly among widowed individuals and females. No direct correlation was found between communication preferences and distress. Conclusions: These findings underscore the importance of shared decision-making, clear information exchange, and a patient-centered approach in the context of ENT cancer care, while also highlighting the need for routine screening and appropriate support for psychological well-being in this patient population.